(untitled) (KYAMC Journal, 2021)
Background: Stroke is the second cause of death and third cause of disability in worldwide so control of risk factor is the best option for prevention of stroke and stroke related disability. Objectives: The study is to know the relation of low serum cholesterol with hemorrhagic stroke. Materials and Methods: This Study is a case control study carried out at Neurology and Medicine ward Mymensingh Medical college hospital (MMCH) from july2017 to December 2018 to see the association of low serum cholesterol with hemorrhagic stroke. A total number of 120 subjects more than 18 years were considered for the study. Among them 60 were study group and 60 were control group. The study population has been selected following some exclusion and inclusion criteria. Results: Result showed that hemorrhagic stroke was more in male than female, common after the age of 60 years. Lower middle classes are more sufferers. Hypertension was 76.7% of study group and serum cholesterol was significantly lower in study group than the control group. Conclusion: This study found that the serum total cholesterol level of study group is less than that of the healthy control group and the difference is statistically highly significant (p< 0.001). So it can be concluded that low serum cholesterol is associated with hemorrhagic stroke. KYAMC Journal. 2021;12(3): 147-152